The Implementation Of Data Mining In Predicting The Number Of Marriages Using Least Squares Method At KUA Ulu Musi - Widian Sulistio; Maryaningsih Maryaningsih; Dimas Aulia Trianggana (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
KUA Ulu Musi Sub-district is one of KUA offices in Empat Lawang Regency that plays an important role in recording and facilitating marriage processes, including issuing permits, recording, and issuing related documents. Until now, data processing at KUA Ulu Musi has been done manually through data recording books, and the number of marriages is written on a board provided as information. Given that the number of marriages fluctuates annually from 2014 to 2023, KUA sometimes faces difficulties in ensuring the availability of documents, managing wedding queues, and preparing the necessary facilities. The implementation of data mining in predicting the number of marriages using the least squares method at KUA Ulu Musi can provide information regarding the predicted number of marriages for the following year, enabling KUA to prepare sufficient administrative staff and personnel to serve prospective couples optimally and avoid case backlogs during certain periods. Based on test data with two data conditions—odd numbers (2014–2022) and even numbers (2014–2023) the predicted number of marriages for 2023 was 166, and for 2024, it was 168. From the accuracy level testing, the accuracy level calculation yielded a MAPE error percentage of 18.43%, indicating good accuracy. This shows that the least squares method is sufficiently reliable in predicting the number of marriages at KUA Ulu Musi.